The modernization of policy-making processes in national sport organizations: A case study of Athletics Canada - Dowling, M.; Denison, J.; Washington, M. (Journal of Amateur Sport, 2015)
This article explores the consequences of modernization on the policy-making processes of a singular National Sport Organization: Athletics Canada. In drawing upon the works of Green and Houlihan (2005) as a baseline comparison we examine how the organizations` policy-making processes have changed over a 10-year period (2002-2012). Specifically, our analysis focuses on the nature and extent of these intra-organizational policy-related changes and how they have influenced the organizations` decision-making capabilities. The descriptive analysis is informed by empirical data collected from eight in-depth semi-structured interviews with senior Athletics Canada personnel and concentrates on three inter-related themes (i) the development and prioritization of OTP-funded policies and programs; and (ii) the development and prioritization of evidence-based policies and programs, which, in turn, has resulted in (iii) increased inter-organizational relationship strain between Athletics Canada and its key delivery partners. More broadly, our investigation contributes to recent amateur sport scholarship that has sought to better understand how these broader socio-political shifts have influenced the specific decision-making processes of sport organizations.